URGENSITAS GURU DALAM PERSPEKTIF PSIKOLOGI DAN ISLAM - Mahmudin, Mahmudin (Sekolah Tinggi Agama Islam (STAI) Al-Ma'rif Buntok, 2023)
The teacher's duty is to think about how efforts are made to improve the quality of learning, including understanding and exploring the material to be delivered, understanding the characteristics of the material and the characteristics of students, making lesson plans carefully and preparing a number of appropriate learning tools. Teachers are required to have academic qualifications, competencies, educator certificates, physically and mentally healthy, and have the ability to realize national education goals. Pedagogic competence, personal competence, social competence, and professional competence obtained through professional education. Whereas in the ministry of religion there are five competencies, namely leadership competence. The function of the teacher today is experiencing development in fostering and educating students to be able to achieve educational goals. Especially in the current school system, the problem of knowledge, skills and skills of teaching staff needs serious attention. However good the curriculum, administration and equipment facilities are, if it is not matched by an increase in the quality of the teachers it will not bring the expected results.